Framework for building a digital visual narrative in journalism:: Inter-American dialogue in knowledge production (Intercom - Brazilian Journal of Communication Sciences, 2026)
This paper proposes the development of a visual narrative for digital journalism. The study addresses the challenge of adapting traditional journalism to the complexity of the Web by employing theories from Emotional Design, Interface Design, and Design Thinking to propose a conceptual framework that guides this process. Through a qualitative methodology - including literature review and interviews with professionals and scholars in the United States and Brazil - the research offers a comparative and interdisciplinary perspective on the production of convergent content for multiple platforms and devices. The conceptual framework, which considers the news (data), the reader (user), and the platform (interface), promotes a user-centered approach to creating fluid and empathetic visual narratives.
Keywords: digital journalism; convergence; visual narrative.